2016
DOI: 10.3892/mmr.2016.5633
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in FGFR2 and TNRC9 genes are associated with breast cancer risk in Pakistani women

Abstract: Single nucleotide polymorphisms (SNPs) lead to genetic differences in breast cancer (BC) susceptibility among women from different ethnicities. The present study aimed at investigating the involvement of SNPs of three genes, including fibroblast growth factor receptor 2 (FGFR2), trinucleotide-repeat-containing 9 (TNRC9) and mitogen-activated protein kinase kinase kinase 1 (MAP3K1), as risk factors for the development of BC. A case‑control study (90‑100 cases; 90‑100 controls) was performed to evaluate five gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
2
7
1
Order By: Relevance
“…The two remaining SNPs, rs2046210 and rs3803662, were found to be associated with breast cancer risk in our Vietnamese cohort, with P values less than 0.007 (Table 6). In addition, these results correlate with other association studies of rs2046210 and rs3803662 in Europeans and Asians, especially Japanese, with P values less than 0.03 and the highest OR (95% CI) being 2.16 (1.32-3.59) (Cai et al, 2011;Mizoo et al, 2013;Mazhar et al, 2016;Wang et al, 2016;Hu et al, 2017). Therefore, these two SNPs are likely to increase the risk of breast cancer up to two-fold in Vietnamese women (Tables 7 and 8), as in other ethnic groups.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The two remaining SNPs, rs2046210 and rs3803662, were found to be associated with breast cancer risk in our Vietnamese cohort, with P values less than 0.007 (Table 6). In addition, these results correlate with other association studies of rs2046210 and rs3803662 in Europeans and Asians, especially Japanese, with P values less than 0.03 and the highest OR (95% CI) being 2.16 (1.32-3.59) (Cai et al, 2011;Mizoo et al, 2013;Mazhar et al, 2016;Wang et al, 2016;Hu et al, 2017). Therefore, these two SNPs are likely to increase the risk of breast cancer up to two-fold in Vietnamese women (Tables 7 and 8), as in other ethnic groups.…”
Section: Discussionsupporting
confidence: 89%
“…Among the genotyped SNPs, five (rs1219648, rs3817198, rs889312, rs10941679 and rs13281615) were found to not show an association with breast cancer risk, but the remaining two (rs2046210 and rs3803662) showed a strong association with the risk of breast cancer in our Vietnamese population cohort. In the literature, five SNPs (rs1219648, rs3817198, rs889312, rs10941679, and rs13281615) were shown to be strongly associated with breast cancer risk in Europeans and Asians (Antoniou et al, 2009;Shan et al, 2012;Wang et al, 2013;Sawyer et al, 2014;Siddiqui et al, 2014;Campa et al, 2015;Ghoussaini et al, 2016;Mazhar et al, 2016;Tang et al, 2016;Zhang et al, 2016;Hein et al, 2017), as well as in populations similar to the Vietnamese, namely Chinese and Taiwanese populations (Liang et al, 2008;Long et al, 2010;Zheng et al, 2010;Kuo et al, 2017). Furthermore, among these populations, these five SNPs have been shown to be associated with an increased risk of breast cancer with the highest OR (95% CI) of 3.06 (1.79-5.25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies conducted in Latin America replicated selected loci that were discovered in breast cancer GWAS conducted in samples of European origin: two in Chile and one in Mexico [95,96,116]. These studies tested the association between SNPs in FGFR2 , TOX3 , and MAP3K1 genes and the 2q35 and 8q24 loci, that were replicated in different populations [178,179,180,181,182,183,184]. FGFR2 and MAP3K1 are tyrosine kinases.…”
Section: Genome-wide Association Studies In Latin Americamentioning
confidence: 96%
“…They demonstrated the functional significance of this intronic variant using a combination of luciferase reporter gene assays and electrophoretic mobility shift assays. Similarly, Mazhar et al reported that two intronic variants of FGFR2 [rs2981582 ( P = 0.005), rs1219648 ( P = 9.08e-006)] and a non-coding transcript of CASC16 [rs3803662 ( P = 0.012)] were related to sporadic breast cancer in Pakistani women [ 12 ].…”
Section: Introductionmentioning
confidence: 99%